The universal furnace units of central frequency for foundry production - V. I. Luzgin; A. Ju. Petrov; S. A. Rachkov; K. V. Jakushev (Литьë и металлургия)
The offered by authors method of the multiple-operator dual-frequency melting of metals allows to expand the technical-economic figures and to provide its higher flexibility and universality as the basic module of foundry production.